Malignant Pericardial Effusion in Lung Adenocarcinoma: When to Escalate from Pericardiocentesis to Open Pericardiostomy - Ibnu Kharisman; Prima Kharisma Hayuningrat (HM Publisher, 2025)
Malignant pericardial effusion (MPE) is a grave, life-limiting complication of advanced cancer, where lung adenocarcinoma is a leading cause. Its management is a cornerstone of palliative cardio-oncology, focused on alleviating debilitating dyspnea and enhancing the quality of remaining life. The optimal therapeutic pathway, especially following the failure of initial interventions, remains a critical challenge, demanding a careful balance between efficacy and treatment burden. A 58-year-old female with stage IV lung adenocarcinoma and a good baseline performance status (ECOG 1) presented with progressive, life-limiting dyspnea (NYHA Class IV). A massive pericardial effusion was diagnosed, and an initial pericardiocentesis provided only transient relief, with severe symptoms recurring within 48 hours. Following a multidisciplinary discussion centered on the patient’s goals of care, the decision was made to escalate to a definitive surgical procedure. A subxiphoid open pericardiostomy was performed, yielding hemorrhagic fluid and pericardial tissue that confirmed metastatic adenocarcinoma. The procedure resulted in complete, durable resolution of her symptoms. In conclusion, open pericardiostomy provides durable relief from the life-limiting dyspnea of MPE, a goal often unachievable with pericardiocentesis alone. For appropriately selected patients with advanced cancer, escalating to a definitive surgical procedure is not merely a treatment for effusion but a crucial intervention to restore function and dignity. This case underscores that for patients with recurrent MPE and adequate performance status, timely surgical intervention is a vital component of effective palliative care, maximizing quality of life.